2023
DOI: 10.3390/ijerph20054328
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators of Health and Well-Being in Informal Caregivers of Dementia Patients: A Qualitative Study

Abstract: Background: Given the dramatic projected increase in Alzheimer’s disease globally and the increased risk of morbidity and mortality for family caregivers of these patients, there is an urgent need to provide more targeted, timely resources to support the health and well-being of these informal caregivers. Few studies have investigated the barriers to health and well-being and potential strategies to facilitate better self-care from the unique perspective of the caregivers themselves. Purpose: This qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…The research results of Connors et al [ 34 ] showed that family caregivers without support or assistance had a higher care load. Over time, family caregivers become additional people and suffer as much as persons with dementia [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research results of Connors et al [ 34 ] showed that family caregivers without support or assistance had a higher care load. Over time, family caregivers become additional people and suffer as much as persons with dementia [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Peng et al [ 39 ], foreign care workers improved the mental fatigue of family caregivers when persons with dementia were lost outside the home. Moreover, family caregivers can receive substantial help from family members and other social groups, which could reduce the burden of caring for persons with dementia and shared care tasks, allowing family caregivers to obtain respite services [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 Undoubtedly, caring for Alzheimer's is challenging and demanding that may lead to the occurrence of difficulties including physical, emotional, and mental exhaustion among caregivers. 11 It is estimated that two-thirds of people with AD live and are cared for by their families worldwide. 12 Specifically in Indonesia, where there are strong traditions of filial piety that demand the Indonesians to respect their family members and take responsibility to care for them when they get old.…”
mentioning
confidence: 99%
“…A study by Baptista et al (2018) on informal caregivers of people with MNCD found that caregivers' coping was influenced by the stages of the disease, meaning caregivers used different coping styles at different times. For example, some caregivers experienced emotional distress immediately after the diagnosis of MNCD in their close relative (Duplantier & Williamson, 2023), whereas other caregivers showed poor coping and depressive symptoms as the disorder progressed to the severe stages and as the period of care increased. The caregivers who used more dysfunctional coping strategies were reported to experience increased caregiver burden (Baptista et al, 2018;Duplantier & Willaimson, 2023).…”
Section: Stress and Coping Theorymentioning
confidence: 99%